2018
DOI: 10.2478/acph-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of ibuprofen for freeze dried parenteral dosage forms

Abstract: Ibuprofen, a weakly acidic non-steroidal anti-inflammatory drug having poor aqueous solubility, is a challenging drug for the development of pharmaceutical formulations, resulting in numerous research attempts focusing on improvement of its solubility and consequently bioavailability. Most studies have been done for solid dosage forms, with very little attention paid to parenterals. Hence, the main purpose of the present study was to enhance ibuprofen solubility as a result of formulation composition and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These results strongly indicate that the use of the freeze-drying technique for the microparticles prepared in this study is a good technique to enhance the solubility of ETO and increase the release rate of ETO at pH 7.4. This finding is in agreement with the previously mentioned study, where the solubility of ibuprofen was significantly enhanced by using the freezedrying technique [37]. Similar results were obtained by Wei et al, who showed enhanced dissolution of microparticles loaded with poorly soluble drug nanocrystals: the hydroxypropyl cellulose (HPC) polymer used as a matrix carrier had a low viscosity.…”
Section: In Vitro Release Study Of the Ethylcellulose Microparticles Loaded With Etosupporting
confidence: 92%
“…These results strongly indicate that the use of the freeze-drying technique for the microparticles prepared in this study is a good technique to enhance the solubility of ETO and increase the release rate of ETO at pH 7.4. This finding is in agreement with the previously mentioned study, where the solubility of ibuprofen was significantly enhanced by using the freezedrying technique [37]. Similar results were obtained by Wei et al, who showed enhanced dissolution of microparticles loaded with poorly soluble drug nanocrystals: the hydroxypropyl cellulose (HPC) polymer used as a matrix carrier had a low viscosity.…”
Section: In Vitro Release Study Of the Ethylcellulose Microparticles Loaded With Etosupporting
confidence: 92%
“… 1 –ibuprofen sodium salt; 2 –ibuprofen; 3 –9-hydroxy ibuprofen; 4 –6,9-dihydroxy ibuprofen; 5 –6-hydroxy ibuprofen; 6 –decarboxylated derivative of 9-hydroxy ibuprofen; 7 –decarboxylated derivative of 6,9-dihydroxy ibuprofen; 8 –decarboxylated derivative of 6-hydroxy ibuprofen. The numbering of IBP atoms proposed by Preskar et al is used [ 88 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Two formulations were prepared with different isotonic agents: sodium chloride (NaCl) and mannitol. Both are commonly used but have very different characteristics (i.e., solubility, crystallization behavior and polymorphism) (4). The quantity of mannitol or NaCl was defined with respect to achieving osmolality criteria in a range of 280-320 mOsmol kg -1 of the reconstituted powder, and the quantity of l-arginine by pH criteria (following the optimal physiological pH of 7.4).…”
Section: Preparation Of Freeze-dried Powdersmentioning
confidence: 99%
“…Various techniques for increasing the aqueous solubility of IBP in oral solid and liquid formulations described in the literature were briefly reviewed in our previous research (4). Each technique exhibits both advantages and disadvantages, and the choice depends on drug characteristics, pharmaceutical dosage form, and route of application (5), which in our case was freeze-dried powder for parenteral application.…”
mentioning
confidence: 99%
See 1 more Smart Citation